THE IMPACT OF THE STABILITY OF THE NATIONAL CURRENCY EXCHANGE RATE AND CHANGES IN THE TRADE BALANCE ON ECONOMIC DEVELOPMENT (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article provides an in-depth analysis of the impact of the stability of Uzbekistan’s national currency exchange rate and changes in the trade balance on the country’s economic development. In recent years, fluctuations in the global market environment, the dynamics of export–import volumes, and exchange rate variations have directly influenced the country’s macroeconomic indicators. The study evaluates the interrelationship between the national currency exchange rate, trade balance, inflation rate, and gross domestic product (GDP) growth based on statistical data. Furthermore, the effectiveness of government-implemented currency liberalization policies, changes in customs tariff measures, and export promotion programs has been examined. The results indicate that ensuring sustainable economic growth requires coordination between exchange rate policy and trade policy.